Special Review: Caught in the Crosshairs. Issue 6 (November 2015) - Ferreira, Bibiana I.; Hill, Richard; Link, Wolfgang
Abstract : Abstract: All drugs have molecular targets; however, this does not mean that they are targeted therapeutics. Only by the interaction with a disease-specific molecule can the drug be classified as a targeted therapeutic. This is often not clearly defined and might refer to several different therapeutic modalities such as genomically targeted therapy, immune checkpoint therapy, or pharmacokinetic targeting. To develop a precise concept of targeted therapy, it is crucial to understand how drugs were discovered and how our rapidly expanding knowledge concerning disease mechanism is driving a fundamental conceptual change in modern drug discovery and development. In combination with the increasingly detailed analysis of disease at an individual patient level, we believe that it is very timely to consider the past and current approaches involved in the development of new medicines and to discuss the paradigm shift in and basic concepts associated with targeted therapies and personalized medicine.